You can change the world : the kids' guide to a better planet - Bell, Lucy (Andrews McMeel Publishing, 2020)
Provides information about protecting the environment, and presents a guide to activities that promote sustainability and recycling. Highlights children from around the world who are working to protect the environment, and includes color illustrations and additional resources.